Safety evaluation of lotilaner in dogs after oral administration as flavoured chewable tablets (Credelio™) - Emmanuelle A. Kuntz; Srinivas Kammanadiminti (Parasites & Vectors, 2017)
Abstract Background Lotilaner (Credelio™, Elanco) is a novel isoxazoline that provides rapid speed of flea and tick knockdown which is sustained for at least 1 month following oral administration to dogs. The safety of lotilaner flavoured chewable tablets was investigated in a randomized, blinded, parallel-group design study in healthy Beagle puppies starting at 8 weeks of age. Lotilaner was administered orally once a month over 8 months at one, three and five times the upper level of the recommended dose range (of 20 to 43 mg/kg). Methods The objective of this study was to determine the safety of lotilaner flavoured chewable tablets in healthy dogs when administered monthly over an extended time period at the highest recommended dose rate, i.e. 1× and at elevated dose rates, i.e. 3× and 5×. Sixteen male and 16 female healthy 8-week-old puppies, weighing ~1.5 to 3.0 kg, were randomized among four groups to be untreated controls or to receive lotilaner at dose rates of 43 mg/kg (1×), 129 mg/kg (3×), or 215 mg/kg (5×) on eight occasions - every 4 weeks over 8 months. The control group was sham-dosed. Study dogs were fed within 30 min prior to treatment. Assessment of safety was based on general health observations, detailed clinical observations, complete physical/neurological examinations, including ophthalmological examinations and clinical pathology evaluations (haematology, clinical chemistry and urinalysis), food and water consumption, body weight, pharmacokinetic blood collections, macroscopic and microscopic examinations. Results Blood concentrations of lotilaner confirmed systemic exposure of all study dogs with the exception of the control group. Lotilaner did not induce any treatment-related effects on body weight, food consumption, opthalmoscopic, physical/neurological and electrocardiographic examinations. For clinical pathology, no changes related to treatment were noted. There were no treatment-related changes in gross examinations. After microscopic examinations, minor findings recorded in kidneys were of no toxicological relevance. Changes in the reproductive tissues were attributed to the peri-pubertal age and growth of the animals. Conclusions Lotilaner was well-tolerated in healthy puppies at 8 week of age when administered once monthly on eight occasion over 8 months at the highest recommended dose and at three and five-fold overdose.